Rural Households’ Credit Access and Loan Amount in Wa Municipality, Ghana - Sekyi, Samuel (International Journal of Economics and Financial Issues, 2017)
This study focused on the determinants of rural households’ access to credit and loan amount. Multistage sampling procedure was used to select a sample of 120 households from the Wa Municipality. Data were collected using structured questionnaire. In the absence of potential sample selection bias, a probit model and Ordinary Least Squares regression were estimated. Empirical results show that gender, age, farming and trading occupations, credit history, and household income are significant determinants of rural households’ credit access. Also, gender, education, marital status, trading, formal sector workers, distance and credit source are significant predictors of loan amount. It is recommended that appropriate educational programmes be designed through promotion of self-financing adult literacy classes and local media to increase awareness and knowledge of households on credit. Additionally, procedure for getting loan should be simplified. Finally, to ease rural credit constraints informal financial institutions should increase their presence in the rural communities. Keywords: Rural households, credit access, loan amount JEL Classifications: C5, D1, D11, D12, G20